Determinants of E-Government Implementation - Bogar, Wilson (International Journal of Information Technology and Education, 2025)
E-Government, as a government policy aimed at achieving good governance, has been implemented by local governments with varying levels of success and has not met the expected goals. Among the various factors that contribute to this, one key factor is the competence of employees who utilize IT as a vital tool for e-government. This study was conducted to analyze the influence of attitudes, perceptions of ease of using IT, and perceptions of the benefits of using IT on IT acceptance. The study used a quantitative approach using explanatory research. The sampling technique employed was stratified proportional random sampling, with sample units or members comprising 95 out of 1930, specifically the State Civil Apparatus (ASN) in Sitaro Islands Regency. The data collection technique was a questionnaire that had been tested and was valid and reliable. Data analysis was multiple regression. The results of the study revealed that attitudes, perceptions of ease of use, and perceptions of the benefits of using IT have a positive and significant effect on IT acceptance, both partially and simultaneously. For this reason, it is necessary to change the attitudes of IT users through their perceptions of IT being difficult to operate and its benefits or results not being much different from without using IT in the context of the public service process, must be changed to the opposite, namely, easy to operate and the results are more effective and efficient.